2020
DOI: 10.1038/s41598-020-68999-9
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cells grown in 3D under fluid flow exhibit an aggressive phenotype and reduced responsiveness to the anti-cancer treatment doxorubicin

Abstract: 3D laboratory models of cancer are designed to recapitulate the biochemical and biophysical characteristics of the tumour microenvironment and aim to enable studies of cancer, and new therapeutic modalities, in a physiologically-relevant manner. We have developed an in vitro 3D model comprising a central high-density mass of breast cancer cells surrounded by collagen type-1 and we incorporated fluid flow and pressure. We noted significant changes in cancer cell behaviour using this system. MDA-MB231 and SKBR3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 52 publications
(52 reference statements)
2
22
0
Order By: Relevance
“…In accordance with other recent evidence collected in different models of 3D-perfused cancer cell culture, 2 , 3 , 22 , 23 , 40 we show that cell proliferation and viability were improved by perfusion at prolonged days of culture, when it is likely that the observed increased number of cells created competition for nutrients and oxygen (Figs. 2 , 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with other recent evidence collected in different models of 3D-perfused cancer cell culture, 2 , 3 , 22 , 23 , 40 we show that cell proliferation and viability were improved by perfusion at prolonged days of culture, when it is likely that the observed increased number of cells created competition for nutrients and oxygen (Figs. 2 , 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…The tumoroid model can be used in combination with other systems to increase stromal biomimicry. Azimi et al (2020) within the Dwek lab at University of Westminster have successfully demonstrated that flow induces an aggressive cancer phenotype with a reduced responsiveness to doxorubicin.…”
Section: Tumoroidsmentioning
confidence: 99%
“…More importantly, the breast cancer cell lines showed resistance to chemotherapy (Paclitaxel) with more surviving cells upon shear stimulation [ 129 ]. In a similar study, Azimi et al demonstrated a reduction in 3D breast cancer sensitivity to Doxorubicin in the presence of a fluid flow environment [ 130 ]. With these studies indicating the role of fluid flow on breast cancer metastasis and resistance to chemotherapy, its effects on radiation response remains unanswered.…”
Section: Current Preclinical Tools To Evaluate Effects Of Radiation Therapymentioning
confidence: 99%